CREED INCREASED ACQUIRED - Bayinat Basha Al-Bajali, Abul Firdaus (IJRDO- Journal of Educational Research, 2023)
This research deals with a set of matters that every Muslim must take into account in order to obtain a good gain, including: the intention, and its role in directing to a good gain, and it is known that the intention in general is a legitimate requirement in all actions, then the doctrine of monotheism and the meaning of the creed in language and idiomatically And the concept of monotheism, and the association of earnings with the monotheism of deism from several aspects, such as: belief that God is the Creator of everything and is the Provider, belief that God Almighty is rich in His creation, and that He, glory be to Him, is the best among His servants in sustenance. Then the hadith touched on the meaning of destiny and destiny and its effect on earning, as it makes a person seek sustenance from his place, lack of haste in livelihood, lack of dependence, and the imperative for the Muslim to be satisfied with what is estimated for him.